2012
DOI: 10.4103/0377-4929.94865
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma of inferior vena cava: A case series of four cases

Abstract: Vascular leiomyosarcomas are rare tumors, arising most frequently from inferior vena cava (IVC). They are mostly seen in sixth decade, with a female predominance. Their diagnosis is often challenging, as patients may present with non-specific complaints such as dyspnea, malaise, weight loss, abdominal pain, or back pain, preceding the diagnosis by several years. Leiomyosarcoma of the IVC most frequently occurs in the middle segment. The final diagnosis can be made by an ultrasound or computed tomography guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…Therefore, nephrectomy, kidney auto-transplantation, or re-attachment of the tumor-free renal vein stump to the re- been established yet because of the insufficient respondence [1,5]. Therefore, there have been several previous reports that the adjuvant chemo-radiotherapy might not have any benefits in patients with complete tumor resection [2,4,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, nephrectomy, kidney auto-transplantation, or re-attachment of the tumor-free renal vein stump to the re- been established yet because of the insufficient respondence [1,5]. Therefore, there have been several previous reports that the adjuvant chemo-radiotherapy might not have any benefits in patients with complete tumor resection [2,4,6].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical diagnosis is usually delayed because the malignancy is often asympto- Survival of the patients with IVC leiomyosarcoma depends on curative tumor resection, its anatomic site, histological grade, invasion of the adjacent structures, and histologic subtype [3]. It has been observed that en bloc surgical resection with negative margins of more than 1 cm is the only treatment that improves survival [3,5]. However, surgical procedures can be complex due to the tumor involvement in the renal vein confluence and at the retrohepatic location.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathology of leiomyosarcoma reveals spindle tumor cells, which are positive for markers of smooth muscle activity including vimentin, muscle actin, alpha-smooth muscle actin and desmin [5]. Material could be obtained by USG or CT guided biopsy or intraoperatively [16]. However, because of nonspecific symptoms, delay in diagnosis is common -33% leiomoysarcomas of IVC is diagnosed at autopsy [17].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor in the upper segment give rise to varying degree of Budd Chiari syndrome due to hepatic vein thrombosis. 3,5 With the development of imaging modalities like USG, CT and MRI, preoperative diagnosis of Leiomyosarcoma is possible. CT scan clearly delineates the intra luminal vascular tumor, which is usually large, lobulated and sometimes heterogeneous owing to haemorrhage and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The final diagnosis can be made by ultrasound or CT guided biopsy. 5,6 Histopathological examination reveals spindle cells arranged in fascicles with variable degree of nuclear atypia and mitotic activity.…”
mentioning
confidence: 99%